2018
DOI: 10.1007/s10943-018-0646-7
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Culture and Meaning-Making Coping: A Study Among Cancer Patients in Turkey

Abstract: The present paper looks at the influence of culture on Turkish cancer patients' use of meaning-making coping, paying particular attention to religious, spiritual, and existential coping methods. Data were collected using an interview study (n = 25, 18 women, age range 20-71). Individuals were recruited at an oncology center and a psychiatry clinic in Istanbul. The main focus of the study has been on existential meaning-making coping, which is characterized by finding power inside oneself, altruism, family love… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 6 publications
4
47
1
3
Order By: Relevance
“…For most Turkish patients in our sample, however, this seemed to be due to thinking it was God-given and unstoppable, whereas German patients saw it as a motivation to change their lives or to be more attentive to their own needs and to appreciate the life and enjoy the moment. Other studies have shown that Turkish patients also use other coping strategies, such as changing priorities in life, but are still guided by basic religious ideas such as “Shukran” (gratitude) [ 15 ]. Psycho-oncological counselling was found to be an important support mechanism for many German patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For most Turkish patients in our sample, however, this seemed to be due to thinking it was God-given and unstoppable, whereas German patients saw it as a motivation to change their lives or to be more attentive to their own needs and to appreciate the life and enjoy the moment. Other studies have shown that Turkish patients also use other coping strategies, such as changing priorities in life, but are still guided by basic religious ideas such as “Shukran” (gratitude) [ 15 ]. Psycho-oncological counselling was found to be an important support mechanism for many German patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, religiosity can also lead to the acceptance of disease-related changes [ 21 ]. On the other hand, a believer may also question his or her faith and feel abandoned by God [ 15 ]. Other studies on coping in Turkish patients show that they benefit from information searches [ 5 , 22 ], social support [ 23 , 24 ], and positive thinking [ 25 ] and, thus, these factors also influence disease prevention [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, affliction with this disease seemed unfair to several women with hard times in life. This problem and such a spiritual perception of the disease leads to spiritual crisis and discontent (29) which can be explained by passive spiritual resources reported by Holt et al (30). They indicated that patients consider God's will as a cause of illness and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this belief could be seen as an impact of the culture of the Malay ethnic group (Mo, 1984). Ahmadi et al (2018b) explains:…”
Section: Demonic Reappraisalmentioning
confidence: 99%